Functional role of the exofacial end of transmembrane domain 6 of the human D1 and D5 dopaminergic receptors - Zamani, Nooshin (University of Ottawa (Canada), 2006)
The molecular basis underlying the distinct ligand binding and activation properties of the dopamine D1 and D5 receptors is not clearly understood. In the present study, I hypothesize that the variant residues of the exofacial end of the transmembrane 6 (TM6) region of Dl and D5 (Ile 294/Leu295 in D1 and Met318/Val 319 in D5) regulate the ligand binding affinity and activation of these two receptors. Chimeric D1R and D5R harboring wild type counterpart variant TM6 residues along with the entire third extracellular loop (EL3) were engineered using PCR and expressed in HEK293 cells. My results show that variant TM6 residues play an important role in controlling the phenotypic expression of EL3-mediated regulation of ligand binding and G protein coupling properties of the human D1 and D5 receptors. These studies may prove useful in the design of subtype-selective drugs for the treatment of pathologies displaying DI-like receptor abnormalities.
Keywords: Biology, Neuroscience.